2014
DOI: 10.1016/j.nlm.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptualization of retrohippocampal contributions to learning and memory

Abstract: A wealth of data supports the notion that the hippocampus binds objects and events together in place and time. In support of this function, a cortical circuit that includes the retrosplenial cortex (RSC) and various structures in the parahippocampal region is thought to provide the hippocampus with essential information regarding the physical and temporal context in which the object/event occurs. However, it remains unclear if and how individual components of this so-called ‘where’ circuit make unique contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 135 publications
(176 reference statements)
7
47
0
Order By: Relevance
“…To date, most studies have focused on the involvement of RSC in spatial and contextual memory (for reviews, see Vann et al 2009;Bucci and Robinson 2014;Miller et al 2014;, given the known connectivity between RSC and visuo-spatial cortical regions (van Groen and Wyss 1990, 1992, 2003. Here we extend this work by demonstrating for the first time that manipulations of RSC impair remote memory for discrete auditory cues.…”
Section: Discussionsupporting
confidence: 61%
“…To date, most studies have focused on the involvement of RSC in spatial and contextual memory (for reviews, see Vann et al 2009;Bucci and Robinson 2014;Miller et al 2014;, given the known connectivity between RSC and visuo-spatial cortical regions (van Groen and Wyss 1990, 1992, 2003. Here we extend this work by demonstrating for the first time that manipulations of RSC impair remote memory for discrete auditory cues.…”
Section: Discussionsupporting
confidence: 61%
“…Although it unclear why trace fear conditioning recruits the RSC in addition to the prefrontal cortex and hippocampus, it is possible that the complex temporal relationship between the CS and UCS in trace conditioning is processed by the RSC. Indeed, the RSC is thought to be a key structure in the where/when pathway, delivering information about the physical and temporal context to the hippocampus (Bucci & Robinson, 2014; Todd & Bucci, In Press). It is therefore tempting to speculate that when the demands of the learning task require significant where/when processing, as occurs in trace or context fear conditioning, the RSC is recruited for acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the RSC receives input from both visual and auditory sensory cortices suggests that it is well-placed to contribute to learning and memory in situations that require processing multiple stimuli from different modalities. Indeed, it has been suggested that the RSC is specifically involved in forming associations between multiple stimuli, or stimulus-stimulus (S-S) learning (e.g., Bucci & Robinson, 2014). Consistent with this idea, two previous studies from our lab have demonstrated a role for the RSC in a different form of higher-order conditioning, sensory preconditioning (e.g., Robinson et al, 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has demonstrated that the retrosplenial cortex (RSC) makes important contributions to spatial and contextual learning and memory (for reviews see Bucci & Robinson, 2014; Miller, Vedder, Law, & Smith, 2014; Todd & Bucci, 2015; Vann, Aggleton, & Maguire, 2009). For example, the RSC is necessary for acquisition and retrieval of contextual fear conditioning (Corcoran et al, 2011; Keene & Bucci, 2008a, 2008c; Kwapis et al, 2015), as well as encoding and retrieval of spatial information (Czajkowski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation